PERFORMANCE ANALYSIS OF THE INTERSECTION OF FOUR VETERAN ROADS, MARABAHAN DISTRICT, BARITO KUALA REGENCY - Fitriani, Anita; Widayanti, Nova (CERUCUK, 2026)
The population and motor vehicle growth in Marabahan City, South Kalimantan, as a result of the designation of East Kalimantan as the new capital of Indonesia, has led to a significant increase in traffic volume, particularly at the Marabahan four-leg intersection—a non-signalized intersection that serves as a key route for community activities during peak hours. This study aims to evaluate the current performance of the intersection, determine when its performance begins to decline, and propose appropriate mitigation measures, using methods based on the 2023 Indonesian Highway Capacity Guidelines (PKJI 2023) and analysis conducted with Excel. Traffic volume data collected over 12 hours on November 24 and 25, 2024, along with population data from Barito Kuala Regency, were analyzed, revealing peak hours on Sunday at 17:00–18:00 and Monday at 07:15–08:15, with an existing performance showing a level of service C. Forecasting indicates a decline in performance to the level of service D by the 14th year,  necessitating intervention. Two alternative solutions are proposed: converting the intersection into a signalized (APILL) intersection with an average delay of 25 seconds/pcu (LOS B) and widening the geometric layout, resulting in a degree of saturation (DS) of 0.873, delay of 16.674 seconds/pcu, queue probability of 45.506%, and maintaining a level of service C.Keywords: Intersection Performance, Indonesian Highway Capacity Guidelines 2023 (PKJI 2023), Signalized Intersection (APILL), Level of Service Index, Capacity, Degree of Saturation.